PENGARUH UKURAN PERUSAHAAN, UKURAN KOMITE AUDIT, DAN UMUR LISTING TERHADAP LUAS PENGUNGKAPAN INTELLECTUAL CAPITAL - Putri Nurmala; Akhmad Sigit Adiwibowo (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2019)
This study aims to determine how much influence the size of the company, the size of the audit committee and the age of the listing of the area of Intellectual Capital Disclosure in companies listed on the Indonesia Stock Exchange in the period 2015-2017. This study uses a sample of manufacturing companies listed on the Stock Exchange in 2015-2017. Sampling using a purposive sampling technique, so that the unit of analysis generated in this study were 31 companies. The data used are secondary data in the form of financial statements obtained from the IDX official website www.idx.com. Data analysis methods used in this study are multiple linear regression analysis, descriptive statistical tests and classic assumption tests. The results of this study indicate that the size of the company, the size of the audit committee and the age of the listing together influence the area of intellectual capital disclosure. Partial test results (t test) show that the size of the company and the size of the audit committee significantly influence the disclosure of intellectual capital, while the age of the listing does not significantly influence the disclosure of intellectual capital.